2000
DOI: 10.1007/s004260000027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spatial and symbolic precues on localization performance

Abstract: One of the fundamental properties of spatial vision is the ability to localize objects in space. According to a recent proposal, accurate localization performance involves the operation of two systems: the attention system and the eye movement system. Upon stimulus presentation, attention is shifted to the target area: this provides coarse location information. Subsequently, a saccadic eye movement is executed: this provides fine location information. In this study we tested predictions derived from this model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…Results demonstrated that, with or without eye movements, localization performance showed the same rapid improvement over the first 50 ms of stimulus duration, whereas thereafter localization accuracy markedly improved in the eye movement condition but not in the no-eye movement condition. The first finding, combined with evidence that the time needed to shift attention is in the order of 50-60 ms (Adam, Huys, van Loon, Kingma, & Paas, 2000), accords with the notion that the attention system is involved in localizing very short duration stimuli. The latter outcome underscores the critical importance of the eye movement system for accurate localization performance.…”
supporting
confidence: 75%
“…Results demonstrated that, with or without eye movements, localization performance showed the same rapid improvement over the first 50 ms of stimulus duration, whereas thereafter localization accuracy markedly improved in the eye movement condition but not in the no-eye movement condition. The first finding, combined with evidence that the time needed to shift attention is in the order of 50-60 ms (Adam, Huys, van Loon, Kingma, & Paas, 2000), accords with the notion that the attention system is involved in localizing very short duration stimuli. The latter outcome underscores the critical importance of the eye movement system for accurate localization performance.…”
supporting
confidence: 75%
“…Specifically, we focus on the impact of identifying a number of digits at fixation on the localization performance of a peripheral target. We will first outline the two-process model of object localization proposed and investigated by Adam, Huys, van Loon, Kingma, & Paas ( 2000 ), Adam et al ( 1993 ); Adam, Paas, Ekering, & van Loon ( 1995 ) (see also Uddin, Ninose, & Nakamizo, 2004 ). We then present an experiment, using a dual-task method, that supports the assertion that visual attention is critical in localizing objects within the first 100 ms.…”
Section: Introductionmentioning
confidence: 99%
“…Ward & Duncan, 1996 , for much longer estimates). In addition, Adam et al ( 2000 ) showed that advance knowledge about the possible location(s) of the target improves localization performance. In particular, they showed that localization performance improved with short duration (i.e., 71 ms) spatial precues, which accords with the notion that the spatial precue quickly directs spatial attention to the target area and thus mediates localization performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the finding that the pair and trio dots conditions led to the best detection of the target can also be explained in terms of reduced spatial uncertainty (Gould, Wolfgang, & Smith, 2007;Salvano-Pardieu et al, 2006). Many studies have demonstrated the ability of spatial cues to direct attention towards a target during a detection task and improve performance (Adam et al, 2008;Adam, Huys, van Loon, Kingma, & Paas, 2000;Hawkins et al, 1990;Henderson, 1991Henderson, , 1996Luck, Hillyard, Mouloua, Woldorff, & Clark, 1994). The fact that detection is facilitated in the dots and Kanizsa conditions relative to the control condition suggests that dots and the inducers of the illusory contour (Pacmen) both serve as spatial cues.…”
Section: Discussionmentioning
confidence: 95%